(untitled) - Eisenhardt, Kathleen M. (Boston, Mass., 2009)
A well written compact little book on the importance of conflict on the building of self leading teams and a simple approach which identifies ways of avoiding productive conflict from becoming useless confrontation.
Keywords: Management,Teams in the workplace,Quản lý,Làm việc nhóm; Psychological aspects,Khía cạnh tâm lý